Lifestyle changes and Nutrition in Polycystic Ovarian Disorder: A Holistic Review - Tiwari, Archita; Verma, Arti; Mishra, Shrishti; Mishra, Bharat (International Journal of Current Innovations in Advanced Research, 2024)
Polycystic Ovarian Disorder (PCOD) is a prevalent endocrine illness in women of reproductive age which is a reproductive and metabolic disorder. It shows hormonal abnormalities in which there is an excessive production of androgens and that is one of the main causes of infertility, diabetes, irregular menstrual periods, hirsutism, hair loss, obesity and acne. One of the main features of PCOD is the presence of cysts on the ovaries, which can affect their ability to release eggs regularly and Anti-Müllerian hormone (AMH) plays an inhibitory role in follicular development and recruitment, contributing to follicular arrest. AMH inhibitory action on FSH-induced aromatase production likely contributes to hyperandrogenism in PCOD. Some factors which can cause of PCOD such as lack of exercise, skipping breakfast, fast food, unbalanced sleep, obesity, genetic, environmental factors and stress level. Lifestyle and nutrition can affect PCOD development and maintenance in PCOD can be done by lifestyle changes such as diet regulation (in taking of vitamins, antioxidant and Creatine) and exercise, as well as medications to regulate hormones, improve fertility and sleep which play a vital role in PCOD management.